The Relationship Between Age and Anemia Status Among Adolescent Girls at the Salafiyah Syafi'iyah Islamic Boarding School in Sukorejo, Situbondo - Ifa Nurhasanah (PROFESSIONAL HEALTH JOURNAL, 2026)
Introduction:  adolescent girls are among the age groups most vulnerable to iron-deficiency anemia. During this period, they experience rapid growth and development, requiring a balanced nutritional intake. One of the essential nutrients needed by the body is iron. In addition, adolescent girls undergo menstruation, which may contribute to the incidence of anemia. Objective:  The purpose of this study was to determine the relationship between respondents' age and their anemia status. Methods:  This study employed a quantitative analysis method with a cross-sectional research design, in which variables were measured simultaneously at a specific point in time. The dependent variable was anemia status, and the independent variable is the respondent's age. The sampling technique used was purposive sampling. The study was conducted at the Salafiyah Syafi’iyah Islamic Boarding School in Sukorejo, Situbondo, with a total of 75 respondents. Univariate analysis presents a frequency distribution of each variable, and bivariate analysis uses the chi-square test because the variables are categorical. Results: The study results show that the majority of participants were early adolescents, totaling 70 individuals (93.3%).  The anemia status in this study showed that most respondents did not have anemia, with 58 individuals (77.3%).  The results of the chi-square test indicate that age is not associated with anemia status. Conclusions:    Age does not have a significant association with anemia status. Nevertheless, it is important to conduct research on this topic, given that anemia status in adolescents is key to improving health outcomes throughout a woman’s life cycle.